2020
DOI: 10.1111/liv.14706
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of tumour mutational burden by targeted next‐generation sequencing as a biomarker in hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
5
20
0
Order By: Relevance
“…Furthermore, PD-L1 positivity was not associated with high TMB, where several patients with high positive PD-L1 were also TMB low (2-5 mutations/Mb)[ 122 ]. These data were confirmed by more recent studies showing that TMB could not predict OS and patient’s responsiveness to anti-PD-1[ 123 - 125 ]. Besides, HCC had low levels of microsatellite instability, a phenotype due to accumulated mutations resulting from a defect in mismatch repair[ 126 ].…”
Section: Biomarkers For Anti-pd-1/pd-l1 Icissupporting
confidence: 68%
“…Furthermore, PD-L1 positivity was not associated with high TMB, where several patients with high positive PD-L1 were also TMB low (2-5 mutations/Mb)[ 122 ]. These data were confirmed by more recent studies showing that TMB could not predict OS and patient’s responsiveness to anti-PD-1[ 123 - 125 ]. Besides, HCC had low levels of microsatellite instability, a phenotype due to accumulated mutations resulting from a defect in mismatch repair[ 126 ].…”
Section: Biomarkers For Anti-pd-1/pd-l1 Icissupporting
confidence: 68%
“…Tissue-agnostic biomarkers such as tumour mutation burden (TMB) and MSI have been examined for cancer immunotherapy [57][58][59]. TMB has been utilised as a predictive biomarker in cancer immunotherapy in several studies [11,[60][61][62]. Our previous study demonstrated significant association of TMB with poor clinical outcomes in HCC patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wong et al evaluated the TMB in 29 HCC patients through targeted next-generation sequencing (tNGS) on both fresh and archival samples. The authors reported that, while fresh HCC samples were better sources of tumor DNA (45), the low median TMB values observed may limit the usefulness of the TMB as a predictor of response to immunotherapy in HCC.…”
Section: Tumor Mutational Burden/microsatellite Instabilitymentioning
confidence: 99%